Solve each equation using the quadratic formula. -4x^2+2x+3=0 相关知识点: 试题来源: 解析 x= (\ 1± √ (13))4 -4x^2+2x+3=0, so a=-4, b=2, c=3.x= (-(2)±√ (2^2-4(-4)(3)))(2(-4))= (-2± √ (52))(-8)= (\ 2± √ 4√ (13))8= (\ 2± 2√ (...
x^2+6x+9=0: 解:x=-3 x^2+7x+10=0: 解:x=-2, x=-5 x^2+4x-21=0: 解:x=-7, x=3反馈 收藏
Solve the following equation with the quadratic formula. 4 b^2 + 8 b + 7 = 4 Solve the following equation using the quadratic formula. 6x2 - x - 40 = 0 Solve the equation for 'x' using the quadratic formula: 4x^2 + 11x - 20 = 0 Solve the following equation using...
Mathematics Tutor With a Master's Degree In Mathematics About this tutor › 3x^2+24x-144 factor out a 3 3(x^2+8x-48) factor 3(x+12)(x-4) but you want to use the quadratic formula (-8±√[64+192])/2 (-8±√256)/2 (-8±16)/2 -24/2 and 8/2 -12 and 4...
The quadratic formula is used to determine the roots of a quadratic equation, written in the form ax2+bx+c=0. The determinant is calculated as D=b2−4ac. If D<0, the roots are imaginary; if D=0, the roots are real and equal; and if D>0, the roots are real and...
解析 You getx= (-b± √ (b^2-4ac))(2a)= (-(5)±√ ((5)^2-4(1)(-3)))(2(1))= (-5± √ (37))2=- 52± (√ (37))2The solution of the equation x^2+5x-3=0 is x such thatx=- 52± (√ (37))2.反馈 收藏 ...
结果1 题目Solve the following quadratic equations by using quadratic formula.(a) 2x^2+3x-4=0(b) -3x^2-4x+1=4x+2x^2-1 相关知识点: 试题来源: 解析 =(-3±√(41))/4 × : (-3+√(41))/4orx=(-3-√(41))/4 反馈 收藏 ...
Step 6: Solve the quadratic equation Using the quadratic formulax=−b±√b2−4ac2a: Here,a=1,b=−3, andc=−1: x=3±√(−3)2−4⋅1⋅(−1)2⋅1 x=3±√9+42 x=3±√132 Final Solutions The complete solutions forxare: ...
Standard Form Equation Random Quadratic Equations Lesson Summary Learning Outcomes Register to view this lesson Are you a student or a teacher? I am a student I am a teacher Claudia F. Teacher Houston, Texas Create an Account I highly recommend you use this site! It helped me pass my ...
The quadratic formula is one of the easiest ways for finding the roots of the quadratic equation of the form {eq}ax^2+bx+c=0 {/eq} as it is very easy to plug the given values into the formula. The quadratic formula is written as {eq}x =\dfrac{-b\pm \sqrt{b...